Multimodal home-based rehabilitation intervention after discharge from inpatient geriatric rehabilitation (GeRas): study protocol for a multicenter randomized controlled trial - Abel, Bastian; Bongartz, Martin; Rapp, Kilian; Roigk, Patrick; Peiter, Janine; Metz, Brigitte; Finger, Benjamin; Büchele, Gisela; Wensing, Michel; Roth, Catharina; Schmidberger, Oliver; König, Hans-Helmut; et al. (BMC geriatrics, 2024)
Geriatric rehabilitation aims to maintain the functional reserves of older adults in order to optimize social participation and prevent disability. After discharge from inpatient geriatric rehabilitation, patients are at high risk for decreased physical capacity, increased vulnerability, and limitations in mobility. As a result, ageing in place becomes uncertain for a plethora of patients after discharge from geriatric rehabilitation and effective strategies to prevent physical decline are required. Collaboration between different health-care providers is essential to improve continuity of care after discharge from inpatient geriatric rehabilitation. The aim of this study is to evaluate the effectiveness of a multi-professional home-based intervention program (GeRas) to improve functional capacity and social participation in older persons after discharge from inpatient geriatric rehabilitation.
Gesehen am 18.03.2024